(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article presents a discussion about process Drama and technologies as educational potentialities considered in teacher training and creative processes with students. This writing aims to reflect on the word technology, as well as its application within the school and how this practice can be related to process Drama, reflecting on the current educational and social context.